Produção rural familiar em Jataí (GO): a Comunidade Rural da Onça - Fockink, Edione Raquel (2007)
This present study aims to understand the family rural production in the Rural Community of Onça, in the town of Jataí (in the Southwest of Goiás State), highlighting the associativism. For the development of this study, it was searched to understand the reorganization of the agrarian space from the agriculture modernization and the main factors which have led the family rural farmers to stay in their properties and resisting the expansion of the great, modern businesslike and mechanized rural production such as the soya beans for exportation. The initial discussion comes from the classic of the Agrarian Geography pointing some definitions and theoretical referencial on the peasant and family production. For the realization of minor rural farmers organization of the Rural Community of Onça, the families associated to the ANPRO (Minor Rural Farmers of the Rural Community of Onça) were researched. In this investigation, it was verified that the insertion in associativism has guaranteed more participation and more income proceeding from dairy production, which is sold to the local dairy company. Also, this study shows that the two centenarian religious celebrations, that happen yearly, are important for the community as a way of the permanency of values and the maintenance of the farmer in the rural space.